2019
DOI: 10.1039/c9ta01718f
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic growth of a sodium metal anode on a pre-patterned current collector for highly rechargeable seawater batteries

Abstract: Deterministic growth of Na metal for highly rechargeable seawater batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…For the NiP@Cu sample, Li + ions nucleate uniformly and follow the epitaxial film growth rather than the dendrite growth model (θ = 0, Figure c) . This demonstrates that the lithiophilicity of the current collector is enhanced, and the NiP modification layer is beneficial to induce more homogeneous lithium deposition, which is consistent with the overpotential deduction in Figure a.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…For the NiP@Cu sample, Li + ions nucleate uniformly and follow the epitaxial film growth rather than the dendrite growth model (θ = 0, Figure c) . This demonstrates that the lithiophilicity of the current collector is enhanced, and the NiP modification layer is beneficial to induce more homogeneous lithium deposition, which is consistent with the overpotential deduction in Figure a.…”
Section: Resultssupporting
confidence: 74%
“…Moreover, the slightly increased thickness to 20 μm (Figure 5m) suggests that fracture of dendrite may occur, further resulting in the accumulation of dead lithium. As suggested by Jung et al, 40 the growth behavior of plating Li on a target substrate can be identified from Young's equation, controlled by the relation of surface energy (γ substrate , γ crystal ), interfacial energy (γ i ), and two-phase contact angle (θ). When the Li growth follows the island-growth model (θ > 0), a highly reactive surface would be inevitably formed and exposed to the organic electrolyte, resulting in continuous side reactions which consume the limited Li inventory and finally leading to dendrite growth, dead lithium, and low CE.…”
Section: Electroless Plating Of Ni−p On a Cu Currentmentioning
confidence: 99%
“…In principle, the formation of sodium dendrites is associated with the nucleation of sodium metal at the initial stage and the following growth after nucleation. ,, The initial nucleation sites play an important role in the subsequent sodium depositing behavior. Thus, the regulation of amount and distribution of initial nucleation sites is crucial to achieve uniform deposition of sodium metal. …”
mentioning
confidence: 99%
“…In addition, PAN matrix with gold (Au) (another guiding element for Na deposition [ 16 ] ) bottom coating (PAN/Au) is also introduced as substrate to verify the effect of the guided layer. [ 16b,17 ] As shown in Figure S15 (Supporting Information), PAN/Au substrates exhibit high Coulombic efficiency of 99.77%, 99.51%, and 98.76% at current density of 1, 2, and 5 mA cm −2 , respectively, in Na plating/stripping cycles, which is much better than that of bare Cu substrate in Figure 3. The symmetric cells with Na‐PAN/Au electrodes also present longer lifespan and lower voltage hysteresis than bare Na electrode (Figure S16, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%